Senile atrophy of the human lacrimal gland: the contribution of chronic inflammatory disease. Issue 9 (September 1984) - Damato, B E; Allan, D; Murray, S B; Lee, W R
Abstract : Histological examination of 99 human lacrimal glands showed a relationship between atrophy of the secretory acini and secretory duct obstruction, ascending periductal fibrosis, and obliteration of the adjacent blood vessels caused by lymphocytic and polymorphonuclear inflammation. Investigation of the subgroups of the B lymphocytic series by immunohistochemistry did not show any statistical change with age, sex, fibrosis, or lymphocytic inflammation. The concept of senile atrophy occurring as a result of senescent involution of the lacrimal gland is challenged on the basis of the histological findings.